2022
DOI: 10.3389/fphar.2022.1064032
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis identifies NT5E as a novel prognostic biomarker on cancer-associated fibroblasts associated with unique tumor microenvironment

Abstract: Background: Ecto-5′-nucleotidase (NT5E) encodes the cluster of differentiation 73 (CD73), whose overexpression contributes to the formation of immunosuppressive tumor microenvironment and is related to exacerbated prognosis, increased risk of metastasis and resistance to immunotherapy of various tumors. However, the prognostic significance of NT5E in pan-cancer is obscure so far.Methods: We explored the expression level of NT5E in cancers and adjacent tissues and revealed the relationship between the NT5E expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
0
0
0
Order By: Relevance
“…Recent studies have shown that tumor‐treating electric fields (TEFT) may exert antitumor effects by influencing the ECM components of the tumor microenvironment (TME) 25,26 . As an important part of the TME, TEFT treatment may regulate the expression patterns of ECM proteins synthesized by tumor cells, inhibit ECM‐mediated pro‐carcinogenic signaling transduction, and ultimately suppress tumor invasion and metastasis 27–29 . Our study found that after screening a range of ECM‐related proteins, collagen type VI alpha 1 (COL6A1) emerged as a key upregulated gene in GBM tissues.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent studies have shown that tumor‐treating electric fields (TEFT) may exert antitumor effects by influencing the ECM components of the tumor microenvironment (TME) 25,26 . As an important part of the TME, TEFT treatment may regulate the expression patterns of ECM proteins synthesized by tumor cells, inhibit ECM‐mediated pro‐carcinogenic signaling transduction, and ultimately suppress tumor invasion and metastasis 27–29 . Our study found that after screening a range of ECM‐related proteins, collagen type VI alpha 1 (COL6A1) emerged as a key upregulated gene in GBM tissues.…”
Section: Introductionmentioning
confidence: 90%
“…25,26 As an important part of the TME, TEFT treatment may regulate the expression patterns of ECM proteins synthesized by tumor cells, inhibit ECMmediated pro-carcinogenic signaling transduction, and ultimately suppress tumor invasion and metastasis. [27][28][29] Our study found that after screening a range of ECM-related proteins, collagen type VI alpha 1 (COL6A1) emerged as a key upregulated gene in GBM tissues. Its high expression was associated with poor prognosis in patients.…”
Section: Introductionmentioning
confidence: 93%
“…Likewise, Xinmiao Xue et al identified NT5E as a novel prognostic biomarker in a pan-cancer analysis. The overexpression of NT5E was related to worse overall survival in UM patients and NT5E was associated positively with the infiltration of cancer-associated fibroblasts (CAFs) through epithelial-mesenchymal transition(EMT) which provided the insight for immunotherapy by targeting EMT (44).…”
Section: Tme and Insight Into Immunotherapymentioning
confidence: 99%